Fluorine‐Free Superhydrophobic Coating: Facile Fabrication of a Mechanical, Chemical, Thermal, and Long‐Term Outdoor Durable Fluorine‐Free Superhydrophobic Coating (Adv. Mater. Interfaces 11/2021). Issue 11 (10th June 2021) - Tan, Xinyu; Wang, Yunkuan; Huang, Zhengtao; Sabin, Sydney; Xiao, Ting; Jiang, Lihua; Chen, Xiaobo
Abstract : In article number 2002209, Xinyu Tan, Xiaobo Chen, and co‐workers demonstrate a fluorine‐free superhydrophobic coating that is prepared using various fabrication methods (e.g., dip‐coating, doctor‐blade painting, spray‐brush). It has impressive mechanical (tested by tape peeling, sand impact, sandpaper abrasion), chemical (pH 1.0–14.0), thermal (up to 550 °C for 2 h) stability, and durable, long‐term outdoor performance with water contact angle of 168.8°, and sliding angle < 1.0°.